Simultaneous Determination of trans-Resveratrol and Emodin in Polygonum cuspidatumRoot Extracts and Pharmaceutical Preparations by High Performance Liquid Chromatography† - B.S. MURTHY, APOLU; S. CHAKRAVARTHY, MANGU; RAMAKRISHNA, TUMMALA; KANNABABU, SUKALA; V. SUBBARAJU, GOTTUMUKKALA (Asian Journal of Chemistry, 2010)
A simultaneous detennination of trans-resveratrol and emodin by high perfonnance liquid chromatography (HPLC) in Polygonum cuspidatum root, extracts and dosage forms was developed and validated. HPLC analysis was performed on a reversed phase C18 column using the gradient formed by 0.1 % (v/v) phosphoric acid in water and acetonitrile at the flow rate of 1 mL/min with photodiode array detection at 280 nm. The linear regression analysis data for the calibration plots for trans-resveratrol and emodin showed good linear relationship with correlation coefficients (r2) 0.9995 ± 0.0002 and 0.9995 ± 0.00025, in the concentration range 0.5-2.0 and 0.25-1.00 μg per injection, respectively. The method . was validated for precision and recovery. The limit of detection (LOD) and limit of quantification (LOQ) were 3.06, 9.27 and 1.03, 3.1 3 ng per injection, respectively, for trans-resveratrol and emodin. Statistical analysis confirmed that the method is accurate, precise and selective and can be applied for the identification and quantification of trans-resveratrol and emodin, simultaneously, in herbal extracts and pharmaceutical preparations.